(untitled) (Annals of Medical Research, 2021)
Aim: Oncological emergencies constitute a considerable part of emergency admissions. The early and correct diagnosis of oncological emergencies increases both life quality and decreases mortality rate due to oncologic emergency. In this study, we evaluated the admissions of oncologic patients to emergency service. Materials and Methods: This study was conducted retrospectively and patients with cancer admitted to emergency service of third degree university hospital between October 2012-2013. Demographic characteristics of the patients, the frequency of admission, admission time, diagnosis, co morbid diseases, and treatment process were investigated. Results: In the study 1472 admission that belongs to 593 patients are assessed. 59,2 % of patients are male, 40.8 % of patients are female. Mean of age is 62. Repeated admission rate is 55.81%. The two most frequent complaints are dyspnea 14.2% and stomachache 10.4%. The two most common types of cancer were lung (19.73%) and stomach (12.47%) cancer. While 64.90% of patients were discharged, 33.80% of patients are hospitalized. The mortality rate in emergency service was 0.1%. Conclusions: Distinguishing the oncological from other emergencies will contribute to patients in terms of reducing mortality and morbidity.